2007
DOI: 10.1161/atvbaha.106.132282
|View full text |Cite
|
Sign up to set email alerts
|

cAMP Signaling in Leukocyte Transendothelial Migration

Abstract: Abstract-The migration of leukocytes across the vascular endothelium is crucial for immunosurveillance as well as for inflammatory responses. Uncontrolled leukocyte transendothelial migration results in pathologies such as asthma, rheumatoid arthritis, and atherosclerosis. The molecular mechanisms that regulate leukocyte transendothelial migration involve signaling downstream of intracellular messengers such as cAMP, calcium, phosphoinositol lipids, or reactive oxygen species. Among these, cAMP is particularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 103 publications
6
83
0
Order By: Relevance
“…It is likely that PKA and PI3K are important components of the migration machine but are controlled separately by other integrin signals. Migration-controlling kinases recruited to the leading front of migrating lymphocytes can facilitate actin polymerization (17,18,37). In agreement with these findings, the confocal images showed that phosphorylated ERK partly colocalized with actin on the leading edge of Jurkat cells.…”
Section: Discussionsupporting
confidence: 82%
“…It is likely that PKA and PI3K are important components of the migration machine but are controlled separately by other integrin signals. Migration-controlling kinases recruited to the leading front of migrating lymphocytes can facilitate actin polymerization (17,18,37). In agreement with these findings, the confocal images showed that phosphorylated ERK partly colocalized with actin on the leading edge of Jurkat cells.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, it seems that cAMP plays a major role in eosinophil migration toward eotaxin per se in agreement with the differential roles that cAMP plays in the complex process of leukocyte migration, depending on the subcellular localization of cAMP production and the relative expression level of different cAMP effectors such as PKA or Epac-1 (exchange protein directly activated by cAMP 1). As recently reviewed by Lorenowicz et al (44), activation of PKA results in inhibition of cell surface expression of selectins and integrins and integrin activation, thereby resulting in reduced adhesion; but PKA is necessary for the clustering of integrins, which is a prerequisite for stable, sustained adhesion. Furthermore, PKA inhibits RhoA, a critical regulator of actin-based contractility.…”
Section: Discussionmentioning
confidence: 98%
“…LTB 4 is clearly chemotactic for neutrophils and macrophages, in part by reducing cAMP levels in migrating cells, similar to chemokines. Of note, elevation of cAMP by various agents inhibits cell migration generally, apparently by PKA phosphorylation of MLCK with a reduction in myosin light-chain phosphorylation and other actions to inhibit lamellipodia formation and extension (292,1076). Other inflammation-amplifying effects of LTB 4 were recently demonstrated in the setting of intermittent hypoxia (1031).…”
Section: -Lo and The Leukotrienesmentioning
confidence: 99%